The value of value addition in coffee production in Uganda - Jun, Minyoung (Kansas State University, 2020)
Coffee is one of Uganda’s most prominent foreign exchange earners and major agricultural exports. The question of how much of the final market price of coffee farmers receive has attracted significant attention by policymakers and researchers. Previous researchers have shown that farmers can increase their share of the final market price for their commodities if they undertake value addition to their commodities. As an export crop, the final price of coffee is complex and therefore difficult to assess farmers’ share of it. Thus, it is unclear whether value addition enhancements for coffee improve farmers’ economic performance in Uganda. The primary objective of this dissertation is to assess the extent to which value addition in coffee improves Uganda coffee farmers’ profitability. Because fresh coffee cherries can deteriorate in quality if not stored properly, and because proper storage of fresh coffee cherries can be difficult, farmers may be motivated to add value to the fresh cherries as risk management strategies instead of securing higher prices for value added products. Either way, the process of adding value is expected to enhance farmers’ profitability. Robusta and Arabica are the two main coffee varieties in Uganda. While some farmers produce only a single variety of coffee, others produce both varieties despite their distinct agronomic requirements. This dissertation explores value addition enhancements undertaken by three types of farmers: (1) those producing only Robusta coffee; (2) those producing only Arabica coffee; and (3) and those producing both varieties simultaneously. Value addition in coffee in Uganda is performed by drying coffee cherries and/or hulling coffee beans. The study then explores the effect of different farmers’ characteristics on their likelihood of undertaking specific value addition activities. Using 2013/14 Uganda National Panel Survey (UNPS) for the analyses, the study’s statistics show that the average coffee prices per kilogram of Robusta fresh cherries, dried cherries, or hulled coffee beans are UGX 1,600; UGX 3,370; and UGX 3,790, respectively. For Arabica, the average prices for fresh cherries, dried cherries and beans were estimated at UGX 1,960, UGX 3,110 and UGX 5,220, respectively. The results of this study show that certain characteristics of farmers make them more likely to undertake value addition. For example, the odds of value addition for Robusta growers was by 5.6 times higher than the odds of value addition for non-Robusta farmers (p < 0.000), ceteris paribus. The marginal probability effect of growing Robusta was estimated as 41% at the means of all other variables in the model. An increase in one hectare of land increased the odds ratio of value addition by 6.9 times higher (p < 0.000). Similarly, an additional year of schooling of the household head increased the odds of adding value by 1.13 times (p < 0.000). This study also confirmed that Arabica is not the dominant coffee variety in Uganda even though it commands a higher price on the market. Growing conditions in Uganda limit farmers’ production of Arabica coffee. This study shows that Robusta growers tend to add value to their products at a higher rate than Arabica growers, and that they subsequently secure a higher percentage of increase in their prices as a result of their value addition activities. The percentage change of price from fresh Robusta cherries to dried Robusta cherries is 111%. On the other hand, the percentage change from fresh Arabica cherries to dried Arabica cherries is only 59%. The percentage changes of price from dried Robusta and Arabica cherries to hulled Robusta and Arabica green beans are 12% and 68%, respectively. Thus, the value addition benefits of selling hulled dried green beans were significantly much higher for Arabica than for Robusta while the benefit of drying fresh cherries seemed better for Robusta. This would suggest that Arabica producers are likely to benefit more from their value adding activities by completing the value addition process, i.e., drying and hulling, instead of stopping at drying, if the option is available to them and is economically feasible.
Keywords: Coffee; Value addition; Robusta; Uganda